Higher performance of constant-reference duo–trio test incorporating affective reference framing in comparison with triangle test - Kim, Min-A; Chae, Ji-Eun; van Hout, Danielle; Lee, Hye-Seong (Food quality and preference, 2014)
•Test performances were compared using the d′ in relation to the operational power.•The constant-reference duo–trio was more operationally powerful than the triangle.•The d′ of duo–trio was improved by using affective framing of constant-reference.•For the balanced-reference triangle test, significant sequence effects were found.•For the constant-reference duo–trio test, sequence effects were not significant. For measuring the sensory discriminability of consumers, ways to optimize the test protocols were investigated in relation to the concept of the test practicality and operational power. Specifically, reference frames using consumers’ affective state of mind and adoption of selective tasting orders of products in a test were designed as the operationally more powerful ways of using consumer discrimination tests. Their effects were investigated in terms of three different versions of the constant-reference duo–trio tests, in comparison to the balanced-reference triangle test as a control protocol. The three different duo–trio protocols were: (1) a duo–trio with a constant-reference of a stronger sample; (2) a duo–trio with a constant-reference of a stronger sample with a fake brand name provided and (3) a duo–trio with a constant-reference of each subject’s preferred sample. Based on signal detection analysis assuming a comparison of distances strategy, all three duo–trio tests were determined to be superior to the triangle test when the first two replications were compared, while only the duo–trio test using the affective reference frame (either with the brand name encoded or with the preferred reference), were found to be superior to the triangle test when all replications were compared. Significant sequence effects were found only for the triangle test. These results indicated that the duo–trio with a constant-reference incorporating the consumers’ state of mind by using the affective reference frames and selective test sequences had the operationally favorable sample sequences and higher test practicality.